2021
DOI: 10.4174/astr.2021.101.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Combined transabdominal and transperineal endoscopic pelvic exenteration for colorectal cancer: feasibility and safety of a two-team approach

Abstract: Purpose Pelvic exenteration (PE) is a highly invasive procedure with high morbidity and mortality rates. Promising options to reduce this invasiveness have included laparoscopic and transperineal approaches. The aim of this study was to identify the safety of combined transabdominal and transperineal endoscopic PE for colorectal malignancies. Methods Fourteen patients who underwent combined transabdominal and transperineal PE (T group: 2-team approach, n = 7; O group: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Histopathological analysis revealed complete excision with clear margins. This combination technique may be subject to further developments [1][2][3][4]. We have demonstrated that simultaneous surgery and the sequential procedure can shorten the operating time.…”
Section: Dear Editormentioning
confidence: 99%
“…Histopathological analysis revealed complete excision with clear margins. This combination technique may be subject to further developments [1][2][3][4]. We have demonstrated that simultaneous surgery and the sequential procedure can shorten the operating time.…”
Section: Dear Editormentioning
confidence: 99%